EFEKTIVITAS PENGAWASAN SEKOLAH DASAR DI KOTA BAU-BAU - Laalisa, Laalisa (Jurnal Pendidikan, 2011)
The teacher profesionalism and accountability must be oriented to increase output quality. School supervising is part of the effort to increase student output and school quality. This research was aimed to elaborate: (1) the school's supervisor intensity in increasing elementary schoolteachers quality; (2) the quality of teachers at elementary school; and (3) the condition of elementary school supervisory management in Bau-Bau City. Data were analyzed descriptively.Results showed that the school's supervising were done regularly once or twice a month in the forms of evaluation and counseling. Teachers' mastery of the teaching skills were good. Mastery of classroom skills is the result of interaction of various factors, and one of these factors is the effectiveness of school supervision. Management factors that influence the regulatory policy of the school classroom teachers quality is generally considered adequate, except for the availability of financial resources which considered inadequate.